2020
DOI: 10.3390/biology9040077
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Male Infertility: Causes, Effects in Assisted Reproductive Techniques, and Protective Support of Antioxidants

Abstract: The spermatozoon is a highly specialized cell, whose main function is the transport of the intact male genetic material into the oocyte. During its formation and transit throughout male and female reproductive tracts, sperm cells are internally and externally surrounded by reactive oxygen species (ROS), which are produced from both endogenous and exogenous sources. While low amounts of ROS are known to be necessary for crucial physiological sperm processes, such as acrosome reaction and sperm–oocyte interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 122 publications
0
26
0
2
Order By: Relevance
“…Piperine treatment repressed the production of MDA levels, which may be due to the alkaloids present in piperine scavenging free radicals due to its potent anti-oxidant activity attenuating the MDA level in treatment groups. Enzymatic and non-enzymatic antioxidants are the primary defenders against cytotoxic oxygen radicals by scavenging intermediates of oxygen reduction [ 42 ]. Some anti-oxidants like SOD and CAT protect against lipid peroxidation in tissues by directly eliminating reactive oxygen metabolites like superoxide (O 2 2• ) and hydroxyl ions (OH • ), providing one of the most efficient defensive mechanisms in the biological system against diseases [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Piperine treatment repressed the production of MDA levels, which may be due to the alkaloids present in piperine scavenging free radicals due to its potent anti-oxidant activity attenuating the MDA level in treatment groups. Enzymatic and non-enzymatic antioxidants are the primary defenders against cytotoxic oxygen radicals by scavenging intermediates of oxygen reduction [ 42 ]. Some anti-oxidants like SOD and CAT protect against lipid peroxidation in tissues by directly eliminating reactive oxygen metabolites like superoxide (O 2 2• ) and hydroxyl ions (OH • ), providing one of the most efficient defensive mechanisms in the biological system against diseases [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a similar relationship between sORP and SDF suggests that, similarly to what has been commented on the previous paragraph, the incorporation of antioxidants in seminal plasma compensates for testicular ROS levels. High levels of ROS can be offset by high levels of antioxidants that prevent SDF generation, and conversely, basal ROS levels along with a decrease in seminal antioxidants could lead to increased SDF [17][18][19][20]. The SDF generated by ROS occurs mainly in the epididymis and vas deferens but not in the ejaculation stage [57][58][59].…”
Section: Sperm Parameters Relationshipmentioning
confidence: 99%
“…Over recent decades, a number of studies have shown that redox deregulation, either by an increase in reactive oxygen species (ROS) or a decrease in antioxidant activity, results in alterations in sperm motility, lipid peroxidation or sperm DNA fragmentation (SDF) [13][14][15][16]. Additionally, several works have described that infertile men have higher concentrations of ROS and lower levels of antioxidants [17][18][19][20]. Oxidative stress (OS) assessments are usually based on ROS level measurements in seminal plasma, but antioxidant levels, which can offset or exacerbate this cellular stress, are not usually calculated.…”
Section: Introductionmentioning
confidence: 99%
“…Это также одна из причин неразвивающейся беременности, спонтанного аборта и неудачных попыток экстракорпорального оплодотворения [7][8][9][10]. Так как окислительный стресс является ведущим механизмом повреждения генетического материала сперматозоидов, антиоксидантная терапия была предложена в качестве одного из основных методов лечения мужского бесплодия, ассоциированного с высоким уровнем фрагментации ДНК сперматозоидов [11][12][13][14][15][16]. В исследованиях оценена эффективность многих антиоксидантов, однако полученные результаты противоречивы [14,[16][17][18][19][20].…”
Section: Introductionunclassified
“…Применение ПНЖК в клинических исследованиях снижало интенсивность воспалительной симптоматики и улучшало состояние пациентов с болезнью Крона, ревматоидным артритом, кератоконъюнктивитом, периодонтитом и гингивитом [40][41][42][43][44]. Окислительный стресс считается основным механизмом повреждения генетического материала сперматозоидов, а главным источником активных форм кислорода в эякуляте являются лейкоциты [11][12][13][45][46][47]. Воспалительный процесс в добавочных половых железах обусловливает повышение концентрации лейкоцитов в эякуляте и, таким образом, может становиться причиной повышения продукции АФК и развития окислительного стресса [45][46][47].…”
Section: Introductionunclassified